Synthesis and characterization of biodegradable Poly(butyl cyanoacrylate) for drug delivery applications - Keller, Benjamin-Luca; Lohmann, Claudia A.; Kyeremateng, Samuel Oppong; Fricker, Gert (Polymers, 2022)
Poly(butyl cyanoacrylate) (PBCA) is a biodegradable and biocompatible homopolymer which is used as a carrier matrix for drug delivery systems in the pharmaceutical industry. Typically, polymerization is carried out under aqueous conditions and results in molecular weights are mostly lower than 3000 g/mol due to the instability of the high molecular weight PBCA. However, the stability of polymer excipients is a major prerequisite for drug product development in the pharmaceutical industry. In this work, a reliable polymer synthesis strategy for PBCA was designed to control the molecular weight in a nonaqueous polymerization environment. The anionic polymerization process and the impact of key synthesis parameters were investigated. The results confirmed that the previously postulated depolymerization-repolymerization process (DPRP) in the literature can be used to tailor the molecular weight of PBCA. The amount of sodium methoxide present during the polymerization proved to be the key parameter to control the DPRP and the molecular weight as desired. In addition, it was discovered that end-capping the PBCA chain suppressed the DPRP and prevented monomer release by depriving the PBCA of its living character. Thus, neat PBCA polymer with varying molecular weights determined by Advanced Polymer Chromatography™ as well as end-capped PBCA were synthesized, and the improvement of the chemical and shelf-life stability were confirmed using NMR.
Gesehen am 28.06.2022